Elaboration of Batik Pattern Design Application in Indonesia - Dinata, Rizky; Fan, Zhang (Universitas Mercu Buana, 2019)
Batik is cultural expression that contains symbolic meaning of philosophy and high aesthetic value for Indonesian people. The unique method makes Batik represent Indonesian unique character. As it application expanding, unfortunately modernization has brought incorrect interpretation about history existence of Batik design and application, it leads to a major problem in philosophy meaning and design innovation of modern Batik. Most of previous researcher only focus on the technique to preserve the method in producing Batik. Focusing in Batik motif and pattern design is required. By formulating a good structural connection from the philosophy of an object and its symbolic meaning, this paper will discuss Batik motif and pattern design which suitable for modern design application. This paper offering a comparative study of three category of development which applied philosophy, contemporary style and basic design principle approach to design a modern batik pattern. New improvement on designing a new modern Batik motif design are essential to applied on innovative product which contain a good philosophy in order to create a strong and consistent message to the target market. So it can brought Batik to the modernization and international market with the high appreciation to Indonesian traditional culture.